Human Resource Management : Theory and Practice - Bratton, John.; Gold, Jeffrey, 1955- (Basingstoke : Palgrave Macmillan, 2007)
This accessible yet challenging text provides a comprehensive introduction to HRM. With a good balance of theory and practice, the text critically evaluates current developments in the subject, such as strategy and the impact of technology.
Previous ed.: 2003.
Includes bibliographical references (p. 589-630) and index.
Keywords: Personnel management; Business and Management